2019
DOI: 10.1111/joim.12912
|View full text |Cite
|
Sign up to set email alerts
|

Neural stimulations regulate the infiltration of immune cells into the CNS

Abstract: The systemic regulation of immune reactions by the nervous system is well studied and depends on the release of hormones. Some regional regulations of immune reactions, on the other hand, depend on specific neural pathways. Better understanding of these regulations will expand therapeutic applications for neuroimmune and organ‐to‐organ functional interactions. Here, we discuss one regional neuroimmune interaction, the gateway reflex, which converts specific neural inputs into local inflammatory outputs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…Some studies confirm that electrical stimulation of the vagus nerve controls exacerbated inflammatory responses 33 , such as in rheumatoid arthritis and Crohn’s disease 34 , 35 . Other neuroimmune pathways and bioelectronics approaches involving autonomic signaling have been studied in inflammatory conditions 36 38 . In contrast, other studies have demonstrated that autonomic dysfunctions are involved in the pathophysiology of different immunosuppressed and cardiovascular conditions mediated by neuroimmune circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies confirm that electrical stimulation of the vagus nerve controls exacerbated inflammatory responses 33 , such as in rheumatoid arthritis and Crohn’s disease 34 , 35 . Other neuroimmune pathways and bioelectronics approaches involving autonomic signaling have been studied in inflammatory conditions 36 38 . In contrast, other studies have demonstrated that autonomic dysfunctions are involved in the pathophysiology of different immunosuppressed and cardiovascular conditions mediated by neuroimmune circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of CNS function can be induced by depleting peripheral CD4 + T cells ( Bauer et al, 2007 ; Wolf et al, 2009 ; Kipnis et al, 2012 ). This leads to hippocampal neuronal loss and reduced cognition which is prevented by IL-4, indicating that neuronal viability and functional integrity are maintained by immune mediators secreted by peripheral lymphocytes ( Kipnis et al, 2012 ; Kamimura and Murakami, 2019 ). Many such influences are probably mediated by the itinerant leukocyte populations passing through the CNS parenchyma.…”
Section: An Integrated Kynurenine-cytokine Systemmentioning
confidence: 99%
“…It has been suggested that the level of local neural activity influences cytokine production and receptor expression which then generate a differential attraction of immune system cells into the CNS, further linking neural activity with neuroimmune communication ( Kamimura and Murakami, 2019 ). Such a mechanism could well be a factor in refining these concepts.…”
Section: Structural and Functional Factors Underlying Cytokine-kynure...mentioning
confidence: 99%
“…Recent data indicate that specific sensory nerves control the permeability of the blood–brain barrier at specific locations and may thus control the entry of immune cell populations into the central nervous system . Kamimura & Murakami in this issue describe a ‘ gateway reflex ’ in which sensory input through specific neural conduits regulates chemokine expression and blood–brain‐barrier integrity in ways that control immune cell entry into the CNS.…”
mentioning
confidence: 99%